Study the Variation of Gamma - Ray Backscattered Count Rate for Halley’s Nucleus - Kadhim, Alaa; Mahdi, Heba (Iraqi Journal of Science, 2024)
In this paper, the single scatter model for gamma backscatter densitometer has been used to investigate the materials of Halley’s nucleus. Monte Carlo simulation tool is used for the evaluation and calibration of gamma backscatter densitometer; and also used to calculate the bulk density. A set of parameters effecting detected count rate of γ – ray backscattering, mainly the source energy, the source – detector separation (sonde length), density and composition, were calculated.Results obtained with the present method are compared with experimental data and the computed data may be considered entirely satisfactory.